In-Plane Strengthening Effect of Prefabricated Concrete Walls on Masonry Structures: Shaking Table Test - Weiwei Li; Weiqing Liu; Shuguang Wang; Dongsheng Du (Shock and Vibration)
The improvement effect of a new strengthening strategy on dynamic action of masonry structure, by installing prefabricated concrete walls on the outer facades, is validated by shaking table test presented in this paper. We carried out dynamic tests of two geometrically identical five-story reduced scaled models, including an unstrengthened and a strengthened masonry model. The experimental analysis encompasses seismic performances such as cracking patterns, failure mechanisms, amplification factors of acceleration, and displacements. The results show that the strengthened masonry structure shows much more excellent seismic capacity when compared with the unstrengthened one.